The Dilemma of HER2 Double-equivocal Breast Carcinomas: Genomic Profiling and Implications for Treatment. (September 2018) - Marchiò, Caterina; Dell'Orto, Patrizia; Annaratone, Laura; Geyer, Felipe C.; Venesio, Tiziana; Berrino, Enrico; Verdun di Cantogno, Ludovica; Garofoli, Andrea; Rangel, Nelson; Casorzo, Laura; dell'Aglio, Carmine; Gugliotta, Patrizia; et al.
Abstract : The American Society of Clinical Oncology/College of American Pathologists (ASCO/CAP) 2013 guidelines for HER2 assessment have increased the number of HER2 equivocal breast carcinomas following in situ hybridization reflex testing, that is, HER2 "double equivocal" (equivocal protein expression and equivocal gene copy number). Forty-five double-equivocal carcinomas were subjected to Prosigna analysis. Twenty-seven cases were investigated for the expression of genes found to be differentially expressed between estrogen receptor (ER)-positive/HER2-positive (N=22) and ER-positive/HER2-negative (N=22) control cases. Twenty-nine of the 45 cases were also analyzed by targeted sequencing using a panel of 14 genes. We then explored the pathologic complete response rates in an independent series of double-equivocal carcinoma patients treated with trastuzumab-containing chemotherapy. All cases were ER-positive, with a mean Ki67 of 28%. Double-equivocal carcinomas were predominantly luminal B (76%); 9 cases (20%) were luminal A, and 2 cases (4%) HER2-enriched. The majority (73%) showed a high risk of recurrence by Prosigna, even when the carcinomas were small (<2 cm), node-negative/micrometastatic, and/or grade 2. Double-equivocal carcinomas showed TP53 (6/29, 20%), PIK3CA (3/29, 10%), HER2 (1/29, 3%), and MAP2K4 (1/29, 3%) mutations. Compared with grade-matched ER-positive/HER2-negative breast carcinomas from METABRIC, double-equivocal carcinomas harbored more frequently TP53 mutations and less frequently PIK3CA mutations ( P <0.05). No significant differences were observed with grade-matched ER-positive/HER2-positive carcinomas. Lower pathologic complete response rates were observed in double-equivocal compared with HER2-positive patients (10% vs. 60%, P =0.009). Double-equivocal carcinomas are preferentially luminal B and show a high risk of recurrence. A subset of these tumors can be labeled as HER2-enriched by transcriptomic analysis. HER2 mutations can be identified in HER2 double-equivocal cases. Abstract : Supplemental Digital Content is available in the text.